2013
DOI: 10.1080/02560046.2013.766972
|View full text |Cite
|
Sign up to set email alerts
|

Masculinity matters: using entertainment education to engage men in ending violence against women in India

Abstract: In this article, R.W. Connell's notion of hegemonic masculinity is used to examine the role of male gender norms in perpetuating violence against women. The researchers discuss the implications for entertainment-education (EE) programmes that seek to promote gender equality by modelling alternative forms of masculinity and sparking critical dialogue about gender-equitable masculine norms. First, theories are reviewed that contextualise masculinity and media to establish a strategic foundation for engaging men … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…EE has been used to explore a wide array of health concerns, perhaps most notably in developing countries (Kawamura & Kohler, 2013; Singhal, 2013). Typically, this can involve examining a health theme, such as HIV, condom use, or domestic violence through a radio or television soap opera (e.g., Goldstein, Usdin, Scheepers, & Japhet, 2005; Lapsansky & Chatterjee, 2013; Pappas-DeLuca et al, 2008; Singhal & Rogers, 1999). It has been suggested that EE works through a variety of processes including narrative-transportation, wherein audiences lose themselves in a story, as well as their involvement with both the storyline and the characters (Moyer-Gusé, 2008).…”
mentioning
confidence: 99%
“…EE has been used to explore a wide array of health concerns, perhaps most notably in developing countries (Kawamura & Kohler, 2013; Singhal, 2013). Typically, this can involve examining a health theme, such as HIV, condom use, or domestic violence through a radio or television soap opera (e.g., Goldstein, Usdin, Scheepers, & Japhet, 2005; Lapsansky & Chatterjee, 2013; Pappas-DeLuca et al, 2008; Singhal & Rogers, 1999). It has been suggested that EE works through a variety of processes including narrative-transportation, wherein audiences lose themselves in a story, as well as their involvement with both the storyline and the characters (Moyer-Gusé, 2008).…”
mentioning
confidence: 99%
“…On the contrary, communities with more gender-equal cultural norms are characterized by alternative forms of masculinity (Flecha García, Puigvert Mallart, & Ríos González, 2013;Giuliano, 2020;Lapsansky & Chatterjee, 2013) and are less keen on justifying abuse.…”
Section: A Cultural Norms and Female Political Representatives At The...mentioning
confidence: 99%
“…Of the fifty-eight programs reviewed, seventy-seven were considered to be “gender-transformative.” That is, they aimed to change the “relations, norms, and systems that sustain gender inequality and violence” ( Barker, Ricardo, and Nascimento 2007: 4 ; Jewkes, Flood, and Lang 2015 ). In the Indian context, programs with men have engaged in peer education and awareness ( Verma et al 2006 ), involved local coalitions of activists and activist-inspired groups ( Das et al 2012 ), and mass-media and awareness campaigns ( Lapsansky and Chatterjee 2013 ), and have shown success in promoting gender equitable norms among men. Global exploratory research with men engaged in anti-violence activism has shown that male allies emphasize the importance of personal relationships with women as well as with other men and their engagement in other social justice movements as important pathways to activism ( E. Casey and Smith 2010 ; E. A. Casey et al 2016 ).…”
Section: Engaging Men: Interventions Allyship and Challengesmentioning
confidence: 99%